(untitled) (Afaq Lughawiyyah, 2024)
This article is related to the exploring TikTok’s role in enhancing Arabic Communication among students in Universiti Sains Islam Malaysia. Specifically, this study aims to find out the factors of students’ inclination towards the TikTok application in communication in Arabic. This research method is implemented using a quantitative descriptive method using a set of questionnaires generated through a Google Form that can collect data related to this study. The Statistical Package For Social Science (SPSS) software was used to measure the acceptability of this study. It covers aspects of students’ challenges in communicating in Arabic in general, even identifying the level of students’ tendencies and also knowing the effect of using TikTok in Arabic communication. As for the results of the study, a total of 60 respondents included 35 males (58.3%) and 25 females (41.7%) for the analysis of the TikTok application in students’ communication skills in Arabic. In conclusion, the use of the TikTok application in Arabic language communication skills is a critical component that makes USIM students more effective when they engage in those skills. The implementation of this study is expected to enable researchers to enrich the success of applications such as TikTok for their benefits in the future.